Resenhas - Fróes, Anelise; Pinsky, Carla Bassanezi; Luna, Naara; Pereira, Ondina Pena; Lessa, Patrícia; Votre, Sebastião; Borba, Rodrigo; Romariz, Sandra Bellas de; Gomes, Simone M. F.; Job, Sandra Maria (Revista Estudos Feministas, 2007)
Resenhas